Analisis Ijārah, Wadī’ah dan Maslahah terhadap Transaksi Penyimpanan Darah Tali Pusat Bayi di Rumah Sakit Mitra Keluarga Darmo Satelit Surabaya - Holis Holis (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2021)
This research is field research that discusses the transaction of storing a baby's umbilical cord blood that occurs at the Darmo Satelit-Surabaya